A Cross-Sectional Study Examined the Relationship between Vitamin D Deficiency and Adult Depression, Anxiety, Stress, Sleep Disturbance, Fatigue, and Quality of Life in India - Madagoni*, Saicharan (Journal of Pharmacy Practice and Community Medicine, 2026)
Background: Vitamin D deficiency is a pervasive public health concern in India, with reported prevalence rates of 70-90%. Emerging evidence suggests a relationship between hypovitaminosis D and psychiatric morbidity; however, comprehensive data examining multiple mental health domains simultaneously in the Indian context remain sparse. Objectives: To evaluate the association between serum 25-hydroxyvitamin D [25(OH)D] levels and depression, anxiety, perceived stress, sleep disturbance, fatigue, and health-related quality of life among Indian adults aged 18-40 years. Materials and Methods: This cross-sectional analytical study enrolled 110 participants from urban and semi-urban settings. Serum 25(OH)D was measured using ECLIA. Depression (PHQ-9), anxiety (GAD-7), stress (PSS-10), Insomnia (ISI), Fatigue (FSS), and Quality of Life (WHOQOL-BREF) were assessed. Data were analysed using ANOVA, correlations, multiple linear regression, and logistic regression. Results: Mean serum 25(OH)D was 19.2 +/-11.3 ng/mL, with 86.4% classified as deficient or insufficient. Vitamin D was significantly inversely correlated with PHQ-9 (r=-0.462, p<0.001), GAD-7 (r=-0.426, p<0.001), PSS-10 (r=-0.240, p=0.012), ISI (r=- 0.266, p=0.005), FSS (r=-0.472, p<0.001), and positively with WHOQOL-BREF (r=0.300, p=0.001). Vitamin D independently predicted depression (beta=-0.131, p<0.001). Logistic regression: aOR=0.89 (95% CI: 0.82-0.96, p=0.004) for moderate-severe depression. Conclusion: Vitamin D deficiency is significantly associated with worse mental health outcomes among Indian adults. Routine screening and supplementation strategies warrant consideration in mental health practice.
Keywords: Anxiety; Cross-sectional study; Depression; Insomnia; Quality of life; Vitamin D; deficiency